2020
DOI: 10.1080/09535314.2020.1752627
|View full text |Cite
|
Sign up to set email alerts
|

Hard times for long-term care systems? Spillover effects on the Spanish economy

Abstract: Since the end of the last century, demographic aging has led to an increased demand for new social protection services. Universalizing these to meet the needs of the most vulnerable requires the design of policies that ensure the sustainability of the system. Consequently, the economic structure of a country and its productive fabric are affected. Assessing the impact of this growing demand is not an easy task, although extended input-output models can help. With this aim, we determine the spillover effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In addition, given that obtaining these figures entails the use of Input–Output models, spillover effects on the different sectors of the economy can be observed. In another study, we showed the importance of the social work activities sector, given its weight within the dependency model, and its low return ( 39 ).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, given that obtaining these figures entails the use of Input–Output models, spillover effects on the different sectors of the economy can be observed. In another study, we showed the importance of the social work activities sector, given its weight within the dependency model, and its low return ( 39 ).…”
Section: Discussionmentioning
confidence: 95%
“…All the above considered, the model applied in this study is built upon a first approach proposed in Bermejo and Del Pozo-Rubio (2019) and Moya-Martínez et al (2020), which was extended here to explicitly consider consumption not only by employed households but also by unemployed households. Both sorts of households were then transferred to the inter-industry transaction matrix, behaving like any other industrial sector but in this case, their input was consumption and their output was labour.…”
Section: Main Frameworkmentioning
confidence: 99%
“…To the best of our knowledge, most of the existing literature has mainly focused on using different econometric models to deal with financing or future spending projections (Moya-Martínez et al 2020). None of the previous studies has estimated the economy-wide effect of LTC spending on the Spanish industry after the structural reform of 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Our assessment of the economic return on the consumption demand sustained by LTC spending grounds on the IO framework is as follows. Basically, we have used the Dependency Extended Input-Output (DEIO) model built in [24] upon the first approach in [22] and [23], which explicitly consider the consumption by employed and unemployed households as an independent component of final demand. The potential of IO models relies on their ability to quantify shifts in production due to demand shocks, as well as to account for the consumption linkages between the industries of an economy.…”
Section: Modelling the Impact Of Public Ltc Spending On The Spanish Economy: Deio Analysismentioning
confidence: 99%
“…As previously mentioned, the 2008 financial crisis caused two structural reforms that were implemented in 2012, introducing austerity measures that affected the LTC system. Recent studies have analyzed how those modifications impacted production derived from LTC spending in the Spanish economy in terms of job creation [22], considering fiscal return [23], and from an industry-wide view [24] by using IO methodology. Initially developed by Leontief as a tool in interindustry analysis [25], IO models allow researchers to analyze the effects produced in the industrial activity by exogenous changes of final demand and by the exchanges of commodities between economic sectors.…”
Section: Introduction 1background and Review Of The Literaturementioning
confidence: 99%